Nuussuarmiut: hunting families on the big headland; demography, subsistence and material culture in Nuussuaq, Upernavik, Northwest Greenland - Hansen, Keld (Museum Tusculanum Press, 2012)
This book describes life in a small hunting community in Northwest Greenland. It is based on fieldwork carried out by the author from 1966 to 1968 and documents in detail the traditional material culture, ways of hunting and fishing, daily life and festive occasions of an Inuit society not yet influenced by European culture. The historical background of the settlement from the establishment in 1923 is outlined, and some indication of what has happened to the small society after the study period is given. Daily life in the settlement itself and out on the hunting grounds is followed day by day through a whole year and all processes are documented in the many original photographs. The book demonstrates a surprising stability in the life of the hunting families, not due to conservatism but because experience has shown them that this way of living is the most suited to the given conditions. At the time of the field study, new tools and a number of other items had been introduced, but these were only adopted when more efficient than those already in use. In a large number of cases they are used in conjunction with the traditional tools.